How did the COVID-19 pandemic affect food environment, food purchase, and fish consumption among low-income urban households in Bangladesh - A path analysis - Akter, Mahsina Syeda; Talsma, Elise F.; Feskens, Edith J.M.; Thilsted, Shakuntala H.; Rasheed, Sabrina (Frontiers Media, 2022)
Background: Animal source foods, especially fish is the most commonly consumed and an important source of macro and micronutrients in the diet of the urban low-income residents. The COVID-19 pandemic has disrupted the food environment in Bangladesh but little is known about how food access and food prices (affordability) have affected the purchase and consumption of fish. The objective of the study was to understand the impact of the first wave of the COVID-19 pandemic on urban food environment with a specific focus on fish consumption.